Parental Involvement on Child’s Education at Home during COVID-19 Pandemic - Bonilla, Marlon Toren; Camo, Jemajo Guban; Lanzaderas, Rhea Alvarez; Lanzaderas, Riza Alvarez; Bonilla, Anita Heredero (International Journal of Humanities and Education Development (IJHED), 2022)
As the COVID-19 pandemic strikes, the Philippine educational system has been interrupted, with regular classrooms being replaced with distance learning. Parents are compelled to act as teachers or tutors in their children's home education. This study aims to find out how parents participate in distance learning at the height of the pandemic. This research used a descriptive-correlational research design. Researcher-made questionnaires were used to collect data from 60 parents chosen through stratified intentional sampling. Data were analyzed using descriptive statistics and Kendall’s Tau B for correlations. Findings revealed that family income and parental educational attainment are related to parental involvement. Parental educational attainment and barriers are quite important. Parental educational attainment and parental involvement with barriers are quite important. Family income with barriers is insignificant. The biggest difficulties that parents found were internet connectivity, lack of devices or gadgets, access to the internet, and difficulty instructing their children at home. It is suggested that the Department of Education adopt and stay current with distance learning education as a supplement to traditional methods of teaching-learning to ensure continuity during difficult times. In every situation, parents must accept the critical role of becoming involved in their child's learning process.